Magnitude of enteric pathogens associated with diarrhea and antibiotic resistance of enteric bacterial pathogens isolated among children under 5 years of age in Bule Hora town, West Guji, Ethiopia - Ashenafi, Girma; Tilahun, Dagnamyelew; Aliyo, Alqeer; Sisay, Biruk (Frontiers in Public Health, 2024)
Background Diarrhea is the second leading cause of morbidity and mortality worldwide among all ages, and one of the leading causes of poor health and premature death in the developing world. Microorganisms, such as viruses, bacteria, and parasites, are responsible for enteric infections among children. Excessive and inappropriate use of antimicrobial drugs and poor infection control practices have transformed antimicrobial resistance into a serious threat to public health worldwide. Therefore, it is essential to investigate the prevalence of enteric pathogens and the antimicrobial susceptibility patterns of bacterial pathogens. Objective Assess the prevalence of enteric pathogens associated with diarrhea in children under 5 years at the Bule Hora Health Facility in 2021. Methods An institution-based cross-sectional study was conducted from May 2021 to July 2021 in a Bule Hora Health Centre and Hospital. A total of 422 children with diarrhea were included in the study in the outpatient department. Sociodemographic and associated factors were evaluated using a pre-tested questionnaire. A sufficient amount of stool specimens was collected following standard microbiological procedures. An antigen detection kit was used to diagnose rotaviruses, parasites were examined using microscopy, and bacterial identification was carried out by culture and biochemical tests. The antibiotic susceptibility test of the bacterial isolates was performed using the Kirby-Bauer disc diffusion method. The data were analyzed using SPSS version 20. The p-value less than 0.05 was declared statistically significant. Results The overall prevalence of enteropathogens in children under 5 years of age was 17%, with no mixed infections detected. Of this, 7.8% of the children’s stool samples contained bacterial pathogens, 5% tested positive for rotavirus, and 4.2% contained intestinal parasites. Unprotected drinking water sources, poor carrier hand washing practices, and poor cleaning of utensils for child feeding were factors significantly associated with the prevalence of enteropathogens. Bacterial isolates have shown a high prevalence of resistance to amoxicillin. Conclusion Therefore, it is important to take steps to reduce the spread of enteric pathogens among children under 5 years practicing good hygiene, ensuring sanitation, and providing clean drinking water. We recommend performing antimicrobial susceptibility tests before prescribing treatment to children with diarrhea.